Avoidance of Hen's Egg Based on IgE Levels Should Be Avoided for Children With Hen's Egg Allergy - Miyagi, Yoshitsune; Yamamoto-Hanada, Kiwako; Ogita, Hiroya; Kiguchi, Tomoyuki; Inuzuka, Yusuke; Toyokuni, Kenji; Nishimura, Koji; Irahara, Makoto; Ishikawa, Fumi; Sato, Miori; Saito-Abe, Mayako; Miyaji, Yumiko; et al. (Frontiers in Pediatrics, 2021)
Background: Although hen’s egg (HE) allergy was thought to be usually resolved by late childhood, majority of HE allergy patients with a high level of egg white (HEW)-specific IgE could not acquire tolerance for HE by age 8 years. Objective: The aim is to investigate whether the avoidance of HE until 6 years of age increased the risk of heated HE allergy at age 6 years. Methods: This was a retrospective case-control study. The HE tolerance children (n=17) and children with low-dose HE reactor [a positive reaction to ≤4 g of heated HEW in oral food challenges (OFCs)] children (n=26) were included based on the results of OFC at 6 years old. Multivariate logistic regression analysis was applied to examine the associations between HE avoidance until age 6 years and HE allergy status confirmed by OFC, adjusting the level of ovomucoid-specific IgE (OM-sIgE) during early infancy. Results: A lower proportion of strict avoidance of HE was observed in the HE tolerance group than in the low-dose HE reactor group (6% vs 46%, p=0.006). OM-sIgE levels in children younger than 2 years old were significantly higher in the low-dose HE reactor group than those in the HE tolerance group (median [interquartile], 26.7 UA/mL [11.9-53.4] vs 7.9 UA/mL [0.35-23.4]; p=0.024). The avoidance of HE until 6 years of age increased the risk of heated HE allergy even after adjusting OM-sIgE levels. Conclusions: Long-term avoidance of HE from infancy increased the risk of heated HE allergy confirmed by OFC at age 6 years.